Venous Thromboembolism Prevention in COVID-19: A Review of Latest Evidences - Muchammad Dzikrul Haq Karimullah; Nisa Amnifolia Niazta; Hiradipta Ardining (Heart Science Journal, 2020)
COVID-19 has become major public health problems, with new cases and deaths growing around the world. COVID-19 has been reportedly associated with hypercoagulable state which can lead to venous thromboembolism (VTE) formation. This condition is also associated with worse outcomes in COVID-19 patients, therefore, it is critical for clinicians to identify this condition and manage it accordingly. VTE formation in COVID-19 occurs through several mechanisms, such as inflammatory reaction leading to hypercoagulable state and vascular dysfunction, direct vascular injury by the virus, and immobilization of the patients. The rate of VTE formation is as high as 31% in ICU patients and 9.2% in general wards patients, and it is also associated with poorer prognosis. Thromboprophylaxis with heparin, particularly low molecular weight heparin (LMWH), has been shown to improve the prognosis in these patients. A careful individual assessment is required to determine which patients will benefit from this therapy, as there are still no sufficient prospective trials to establish guidelines for VTE thromboprophylaxis in COVID-19. The assessment includes laboratory parameters such as PT, platelet count, D-dimer, fibrinogen, and other risk factors incorporated in PADUA risk assessment model (RAM), versus the risk of bleeding incorporated in IMPROVE bleeding RAM.